THEORETICAL APPROACHES TO DETERMINING THE ESSENCE OF DEVELOPMENT OF ECONOMIC POTENTIAL OF TERRITORIES AS A STATE-ADMINISTRATIVE CATEGORY - Ivanov , D. (Theory and Practice of Public Administration, 2020)
The article reveals theoretical approaches to determining the essence of the territories economic potential development as a public administration category.The category “potential” can be considered as a precondition for development at the national, regional and local levels. The local level is the most practical and applied sphere of economic potential development and the personification of the state-administrative category “territory”.Theoretical works of scientists are systematized, which allowed to single out resource (as a set of resources that determine the competitive advantages of the territory), sectoral (the need to concentrate the capabilities of economic sectors located within the administrative-territorial system), institutional (holistic system of hierarchical relationships within the community), system (a single system consisting of a set of defined elements), complex (integration and conceptualization of all components) approaches to the definition of the “territory economic potential”.It has been offered the own vision of interpretation of the category “territory economic potential development” as high-quality irreversible balanced changes of system of interconnected potentials providing rational using of resources, effective functioning of sectors of economy, construction of the ordered public relations capable through synergistic interaction to provide high level of competitiveness in community.According to the author, the components of the territory economic potential development, taking into account the provisions of the threefold concept of sustainable development should be through the development of resource, financial, investment, innovation, labor, social, environmental, organizational, managerial, institutional potentials. The territory economic potential development should be considered as a system where the hierarchically higher system for it will be the economic potential of the region, state and supranational formations.The territory economic potential development is characterized by a certain uniqueness. Accordingly, this process in a separate administrative-territorial unit will take place due to its inherent properties and capabilities.